IMPACT PENGEMBANGAN BISNIS UNIT JASA BOGA TERHADAP EFEKTIFITAS PENGELOLAAN DAN PENGEMBANGAN PONDOK PESANTREN : (Studi Kasus Di Pondok Pesantren Bahrul Ulum Putra) - Shofiyul Fajar Muhammad; Ashlihah (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2021)
This study aims to determine the impact of the business development of the catering service unit on the effectiveness of the management and development of the Bahrul Ulum Putra Islamic boarding school. As well as providing knowledge of what can be imitated from the business, so that it can be used and applied to Islamic boarding schools or other institutions. The type of approach used by the author in this research is to use field research (filed research) using a qualitative approach. Field research is research that is carried out by going directly to find and dig up data in the field. The results obtained in this study are, the Catering Service Unit managed by the Bahrul Ulum Islamic Boarding School can have an impact on; ensuring the quality of food provided to students, increasing the number of students, increasing the level of trust of guardians of students to Islamic boarding schools, the existence of business units that can provide additional financial income at Islamic boarding schools.